2011
DOI: 10.1167/iovs.11-7597
|View full text |Cite
|
Sign up to set email alerts
|

Decoding of Temporal Visual Information from Electrically Evoked Retinal Ganglion Cell Activities in Photoreceptor-Degenerated Retinas

Abstract: PURPOSE.To restore visual function via the prosthetic stimulation of retina, visual information must be properly represented in the electrically evoked neural activity of retinal ganglion cells (RGCs). In this study, the RGC responses in photoreceptor-degenerated retinas were shown to actually encode temporal information on visual input when they were stimulated by biphasic pulse trains with amplitude modulation. METHODS. Multiple RGC spike trains were recorded from rd1 mouse retinal patches mounted on planar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Although the combination of cell-type specificity, spatial and temporal precision, and completeness of electrically elicited activity exceeded the scope of previous work (Nirenberg and Pandarinath, 2012; Jensen et al, 2009; Hottowy et al, 2012; Fried et al, 2006; Ryu et al, 2011), additional work would be required to fully understand the generality and impact of these findings for future epiretinal prostheses, for several reasons.

Although focal activation of individual cells is clearly possible among the dominant RGC types in the primate retina (Sekirnjak et al, 2008; Jepson et al, 2013), and was achieved here in small collections of ON parasol cells, the reliability of activation of one cell without activation of any cells of other types has yet to be fully documented.

…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the combination of cell-type specificity, spatial and temporal precision, and completeness of electrically elicited activity exceeded the scope of previous work (Nirenberg and Pandarinath, 2012; Jensen et al, 2009; Hottowy et al, 2012; Fried et al, 2006; Ryu et al, 2011), additional work would be required to fully understand the generality and impact of these findings for future epiretinal prostheses, for several reasons.

Although focal activation of individual cells is clearly possible among the dominant RGC types in the primate retina (Sekirnjak et al, 2008; Jepson et al, 2013), and was achieved here in small collections of ON parasol cells, the reliability of activation of one cell without activation of any cells of other types has yet to be fully documented.

…”
Section: Discussionmentioning
confidence: 87%
“…Although present-day prostheses produce only limited visual function (Dorn et al, 2013; G. Richard et al, 2008, ARVO abstract; Klauke et al, 2011; Barry and Dagnelie, 2012; Humayun et al, 2012; da Cruz et al, 2013), experiments in isolated retina have demonstrated the capacity to electrically stimulate individual retinal ganglion cells (RGCs) to fire individual spikes (Jensen et al, 2005; Fried et al, 2006) with high spatial and temporal precision (Fried et al, 2006; Sekirnjak et al, 2006; Sekirnjak et al, 2008; Hottowy et al, 2012; Jepson et al, 2013). These findings raise the possibility of faithful reproduction of the neural code of the retina, and thus much more acute artificial vision, with future prostheses (see Jensen et al, 2009; Fried et al, 2006; Ryu et al, 2011). However, it is well known that naturalistic visual experience relies not on the activity of any individual RGC but on diverse spatiotemporal patterns of activity in multiple distinct populations of RGCs.…”
Section: Introductionmentioning
confidence: 85%
“…In our recent studies on temporal information encoding by electrically stimulated RGCs, the pulse amplitude time-series could be successfully reconstructed from evoked RGC activities (67). This is supported by recent reports on human clinical trials of retinal implants, such as the report of Greenwald et al (18), where it was shown that the brightness of the phosphene elicited by electrical stimulation of the retina followed the current amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…The overall procedure for spike train decoding is illustrated in detail in Fig. 2 of Ryu et al (7) and briefly described herein. The raw waveforms from each electrode were transformed into single unit spike trains, and then, the RGC spike trains were transformed to a firing rate time-series by counting the numbers of spikes in 50 ms bins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation